2021
DOI: 10.1371/journal.pntd.0009782
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and semiquantitative detection of soil-transmitted helminth infection in stool using a recombinase polymerase amplification-based assay

Abstract: Background Soil-transmitted helminths (STHs) are parasitic nematodes that inhabit the human intestine. They affect more than 1.5 billion people worldwide, causing physical and cognitive impairment in children. The global strategy to control STH infection includes periodic mass drug administration (MDA) based on the results of diagnostic testing among populations at risk, but the current microscopy method for detecting infection has diminished sensitivity as the intensity of infection decreases. Thus, improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…114 2.2.3 Reverse transcription-recombinase polymerase amplication (RT-RPA). RPA is considered as an alternative nucleic acid detection technique to PCR, 138 which is capable of realizing single-molecule nucleic acid detection at room temperature within 15 min without hardware equipment. 139 The addition of reverse transcriptase to the RPA reaction components enables the detection of RNA viruses in a single tube.…”
Section: Isothermal Nucleic Acid Amplicationmentioning
confidence: 99%
“…114 2.2.3 Reverse transcription-recombinase polymerase amplication (RT-RPA). RPA is considered as an alternative nucleic acid detection technique to PCR, 138 which is capable of realizing single-molecule nucleic acid detection at room temperature within 15 min without hardware equipment. 139 The addition of reverse transcriptase to the RPA reaction components enables the detection of RNA viruses in a single tube.…”
Section: Isothermal Nucleic Acid Amplicationmentioning
confidence: 99%
“…Recombinase polymerase amplification‐lateral flow dipstick (RPA‐LFD) was advantageous, because it was time‐saving, sensitive, cheap, operationally simple and rapid, and can be used outside of the diagnostic lab. RPA or RPA‐LFD assay is used to rapidly detect cyprinid herpesvirus 2 (CyHV‐2) in goldfish (Preena et al., 2022), Vibrio parahaemolyticus in seafood (Geng et al., 2019), Tetracapsuloides Bryosalmonae in salmonids (Soliman et al., 2018), chilli veinal mottle virus (ChiVMV) in tobacco plants (Jiao et al., 2020), fish sex identification in Cynoglossus semilaevis (Nie et al., 2021), and soil‐transmitted helminths in human (Cantera et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that a single molecule of target DNA can be detected with RPA within 30 min . Yet, most successfully developed RPA assays are qualitative with a positive/negative readout for target DNA, and τ d -based quantification from real-time RPA kinetic measurements has found limited success. This partly arises due to the poor control over undesired amplification close to the ambient temperature after initiation . Similarly, a common observation with RPA reactions has been the low and variable yield of amplicons compared to PCR, though the underlying factors contributing to this remain uncharacterized.…”
Section: Introductionmentioning
confidence: 99%